(untitled) (Bangladesh Journal of Urology, 2022)
The Horseshoe kidney is not uncommon entity with an incidence of 0.25% of general population with increased association of genitourinary anomalies. Horseshoe kidney with single ureter is extremely rare. We report a case of a patient with a Horseshoe kidney with a single ureter with stone that was diagnosed incidentally. Bangladesh J. Urol. 2021; 24(1): 110-111